Mapping-Guided Ablation for Persistent Atrial Fibrillation (MAP-AF): A Multicenter, Single-Blind, Randomized Controlled Trial - Takahashi, Yoshihide; Kobori, Atsushi; Hiroshima, Kenichi; Sakamoto, Yuichiro; Kimura, Masaomi; Inaba, Osamu; Tanimoto, Kojiro; Hanazawa, Ryoichi; Hirakawa, Akihiro; Goya, Masahiko; Sasano, Tetsuo (Circulation. Arrhythmia and electrophysiology, 2024)
The clinical outcome of pulmonary vein isolation (PVI) for persistent atrial fibrillation (AF) is suboptimal. Mapping studies have demonstrated atrial sites outside of the pulmonary veins displaying focal activation patterns during AF. We sought to determine whether adding catheter ablation of focal activation sites to PVI improves clinical outcomes of catheter ablation for persistent AF. In this multicenter, randomized, single-blinded trial, we assigned patients with persistent AF to either PVI alone or to mapping-guided ablation of focal activation sites in addition to PVI in a 1:1 ratio. In the mapping-guided group, both atria were mapped after PVI using a Pentaray catheter (Biosense-Webster) and focal activation sites identified by CARTOFINDER (Biosense-Webster) were ablated. The primary end point was freedom from AF or atrial tachycardia without antiarrhythmic drugs beyond a 90-day blanking period. A total of 98 patients were assigned to the mapping-guided group and 102 to the PVI alone group. In the mapping-guided group, focal activation sites were identified at 2.6±0.3 and 2.5±0.2 sites per patient in the left and right atrium, respectively. Patients were followed up for 768.5 (interquartile range, 723.75-915.75) and 755.5 days (interquartile range, 728.5-913.75) in the mapping-guided ablation and the PVI alone groups, respectively. Freedom from AF/atrial tachycardia without antiarrhythmic drugs at 2-year follow-up was 66.8% and 75.2% in the mapping-guided ablation and the PVI alone groups, respectively (hazard ratio, 1.26 [95% CI, 0.76-2.10]; =0.37). Adverse events occurred in 3 patients (3.0%) and none (0%) in the mapping-guided ablation and the PVI alone groups, respectively ( =0.12). In patients with persistent AF, the addition of mapping-guided ablation of focal activation sites to PVI did not improve clinical outcomes compared with PVI alone. URL: https://center6.umin.ac.jp/cgi-open-bin/ctr/index.cgi?function=02; Unique identifier: UMIN000037569.